Predicting spawning bed erosion and longevity : a case study in tributaries to river Vindelälven, northern Sweden - Tylstedt, Viktor (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2013)
Timber floating operations in Scandinavia during the 19th and 20th centuries has contributed to severe negative impacts on riverine ecosystems. Increase in water velocity and lack of stream bed heterogeneity as a result of stream channelization lead to increased bed load transport. Since availability and recruitment of new suitable spawning substrate in Scandinavian watercourses is sparse, spawning habitats for salmonids has become a scarce commodity. Lately, increasingly more attention has been given to the recreation and improvement of brown trout (Salmo trutta) spawning habitats in restoration projects. While much of the research on spawning habitat has been focused on evaluation of the influence that the constructed spawning grounds have on fish populations, few studies have been conducted to evaluate the persistence of these constructions over time. I evaluate erosion of constructed spawning beds as an effect of sediment transport attributable to water discharge. Two easily applicable sediment transport prediction models are applied to spawning beds in restored tributaries to river Vindelälven. I evaluate these as a method to determine suitable locations for construction of spawning beds. I also evaluate erosion of constructed spawning beds attributable to spawning activities by female brown trout by deploying PIT-tag marked pebbles over spawning beds in tributaries to River Vindelälven and use received data to develop a model describing the erosion process. Analyses of erosion attributed to water flow suggest that both models tested in the study needs refinement to be reliable for prediction of erosion in the water systems investigated in this study. The results highlight the complexity of near-bed shear stress and water velocity. The evaluation of spawning bed erosion attributed to spawning activity suggests that there is a spatial heterogeneity in erosion probabilities over a spawning bed. Erosion differed in magnitude between central-, downstream- and upstream sections, though no difference in movement ...